An unusual electrochemical oxidation of phenothiazine dye to phenothiazine-bi-1, 4-quinone derivative (a donor-acceptor type molecular hybrid) on MWCNT surface and its cysteine electrocatalytic oxidation function. (1st January 2016) - Shanmugam, Ranganathan; Barathi, Palani; Zen, Jyh-Myng; Kumar, Annamalai Senthil
Graphical abstract: Highlights: Phenothiazine gets electro-oxidized to phenothiazine-bi-1, 4-quinone on MWCNT. A phenothazine-quinone surface-confined MWCNT modified GCE was prepared. This new single molecular unit behaves as electron donor–acceptor type system. The modified electrode was characterized by XRD, FTIR and Raman spectroscopy. Cysteine electro-catalytic oxidation was demonstrated at low potential. Flow injection analysis of cysteine was studied. Abstract: Phenothiazine (PTZ), a thiazine class heterocyclic compound, is a well-known electron donating system and has been widely used as a starting compound to prepare various phenothiazine dyes and pharmaceutically important compounds. Quinones and its derivatives are constituents of biologically active molecules serve as excellent electron-acceptor systems. Oxidation of PTZ by chemical and electrochemical methods often resulted into monohydroxylation of benzene ring moiety, S-oxidized and polymerized compounds as end products. Electrochemical oxidation of PTZ on a multiwalled carbon nanotube (MWCNT) modified glassy carbon electrode in pH 7 phosphate buffers solution (PBS) has been investigated in this work. A highly redox active surface confined PTZ-bi-1, 4-quinone derivative (PTZ-biQ) on MWCNT modified glassy carbon electrode, designated as GCE/MWCNT@PTZ-biQ, as a product was unusually observed. The GCE/MWCNT@PTZ-biQ showed well-defined redox peaks at E1/2 = −0.07 and +0.29 V vs Ag/AgCl corresponding to surface confined electron-transfer behavior of the bi-quinone (acceptor) and PTZ-cationic radical species (donor) respectively. No such electrochemical characteristics were noticed when unmodified GCE was subjected to the electrochemical oxidation of PTZ. Existence of PTZ-biQ was confirmed by XRD, Raman spectroscopy, FT-IR and GC-MS (methanolic extract of the active layer) analyses. Position of biQ in PTZ-biQ as 1, 4-quinone isomer was confirmed by observation of absence of copper-complexation with 1, 4-quinone and H2 O2 electrochemical reduction reactions at −0.1 V vs Ag/AgCl unlike to the specific copper-complexation and H2 O2 reduction with 1, 2-quinone isomer in pH 7. Cysteine (CySH) oxidation was studied as a model system to understand the electron-transfer function of the MWCNT@PTZ-biQ. A highly selective electrocatalytic oxidation and sensing by amperometric i-t and flow injection analysis of CySH at low oxidation potential, 0.3 V vs Ag/AgCl in pH 7 PBS with detection limit values (signal-to-noise ratio = 3) of 11.10 μM and 110 nM respectively, without any interference from other biochemicals like uric acid, dopamine, nitrite, citric acid and H2 O2, unlike the conventional chemically modified electrodes with serious interference's, have been demonstrated.